PENENTUAN POLA PEMBELIAN OBAT MENGGUNAKAN ALGORITMA APRIORI - Syahrir, Moch; Rismayanti, Ria; Wicaksono, Moh Arief (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
Pharmacy is one of the businesses engaged in the health sector, especially product and services in improving public health. This service is carried out by a pharmacy manager in an effort to fulfill the duties and functions of pharmacy. This causes problems that occur in pharmacies, when search for drugs must be done by looking for one by one in transaction, because the pharmacy manager does not know sure the stock of drugs in the pharmacy. In addition, another problem is the arrangement of irregular drug layouts where the drug placement does not have a good standard layout. The method used in building this system is association with a priori on sales transaction data. then processed in a model to explore valuable information, as a policy standard in running a business. Application testing uses 3 minimum support and confidence values ​​so can get the rule and k-Itemset results from 3 different values.